1988
DOI: 10.1002/art.1780310208
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic assessment and psychologic variables as predictors of pain and functional impairment in osteoarthritis of the knee or hip

Abstract: Sixty‐five outpatients with osteoarthritis of the knee and/or hip were assessed using radiographic ratings of disease severity, measures of psychologic coping, and multidimensional clinical outcomes of degree of pain and functional impairment. Disease severity accounted for little of the individual variability in clinical outcomes. Even after controlling for disease severity, psychologic variables remained strong predictors of individual differences in functional impairment and pain. Psychologic processes dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
150
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(167 citation statements)
references
References 26 publications
(22 reference statements)
14
150
3
Order By: Relevance
“…A relationship between depressive symptoms and physical function has been described in longitudinal studies not limited to individuals with arthritis, as summarized by Ormel et al (46), and in cross-sectional studies of knee OA (31,34,47,48). The demonstration in the current study that the status of mental health predicts subsequent physical function is important, given how function assessment might be biased by depressive symptoms.…”
supporting
confidence: 51%
“…A relationship between depressive symptoms and physical function has been described in longitudinal studies not limited to individuals with arthritis, as summarized by Ormel et al (46), and in cross-sectional studies of knee OA (31,34,47,48). The demonstration in the current study that the status of mental health predicts subsequent physical function is important, given how function assessment might be biased by depressive symptoms.…”
supporting
confidence: 51%
“…Third, we could not consider all factors which potentially confound the correlation between symptom and radiographic severities because this study was performed as a cross-sectional survey in a large cohort. Previous studies suggest many factors including quadriceps power, range of motion, psychosocial factors, comorbidities, or pain medication could influence symptom manifestations of osteoarthritic knees [10,14,28,29,35,37,44]. Fourth, subjects with K/L Grade 4 and severe knee symptoms might have had knee arthroplasty and were not recruited into the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although elderly subjects are vulnerable to OA pain, previous studies have not shown any significant difference between subgroups of OA patients stratified by age (<65 vs >65 years) (18,77), and other researchers have failed to find an association between age and physical function or the presence or severity of pain in OA (78)(79)(80).…”
Section: Agementioning
confidence: 99%